Impact of readability on corporate bond market - Jieyan Fang-Klingler (Journal of Risk and Financial Management, 2019)
This paper investigates the impact of annual report readability on the corporate bond market. My findings indicate that in the US corporate bond market, firms with less readable annual reports tend to have higher credit spreads, higher credit spread volatilities, higher transaction costs, higher transaction costs volatility, smaller trade size, higher number of trades and higher number of trades volatility. This paper also provides the first answers to the question as to whether annual report readability matters to international market participants in the corporate bond market. My findings provide evidence that in the EUR corporate bond market, firms with more readable annual reports are associated with lower credit spreads.
Keywords: 330; annual report; credit spread; readability; spread volatility; textual analysis; transactions costs